Populacijska študija najpogostejših demielinizacijskih bolezni Charcot-Marie-Tooth v Sloveniji - Leonardis, Lea (Zdravniški vestnik, 2003)
Background. The most common genetic defect in demyelinative type of Charcot-Marie-Tooth disease (CMTI) is dominantly inherited duplication of 17p11.2 (CMT1A). Phenotipically rather different, butgenetically related to CMTIA, is hereditary neuropathy with liability to pressure palsies (HNPP) which is linked to deletion of the same part of chromosome 17 as duplication in CMTIA. The aim of our study was to analyse the frequency of duplication anddeletion of Z7p11.2 in CMTI and HNPP Slovene patients, respectively. We also sought for eventual point mutations in connexin 32 (Cx32), protein zero (P0), peripheral myelin protein-22 (PMP22) genes and in N-myc downstream-regulated genel (NDRG1). Methods. Probes pVAW409R3a, pNEA102 and pLR7.8 were used for Southern blotting and primers RM-11 in Mfd-41 for the polymerase chain reaction. Sequencing was used for the demonstration of eventual point mutations. Results and conclusions. The duplication ordeletion of 17p11.2 was found in 76% and 100% of unrelated CMTI and HNPP patients, respectively. Point mutations in P0 were found in 8% of unrelated patients. Ina Gypsy family, point mutation in NDRGI was revealed. The prevalence of CMTIA in Slovenia was found to be 4. 7/100, 000 which is most likely less thantrue average (10/100,000 elsewhere). The Slovene prevalence of HNPP was calculated at 2,2/100,000 (2-16/100.000 elsewhere).
Keywords: Blot, Southern; Blotting, Southern; Charcot-Marie Disease; Chromosome Deletion; Chromosomes, Human, Pair 17; Connexins; dedne bolezni; Epidemiology; Genes, Myc; Genetics; Geni myc; Incidenca; Incidence; Koneksini; Kromosomi človeški, par 17; Kromosomska delecija; Mielinska P0 beljakovina; Mielinske beljakovine; mutacije; Myelin P0 Protein; Myelin Proteins; periferno živčevje; Point Mutation; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Prevalenca; Prevalence; Točkovna mutacija